Which Subjects and Styles Have Been Examined in Islamic Fatwas and Guidelines? - Ramli, Ishak; Mokhtar, Mumtaz; Mohd Zain, D'zul Haimi; Osman, Muhamad Rahimi; Masrek, Mohamad Noorman (Idealogy Journal, 2018)
Visual art is one of the most critical and popular issues explored from an Islamic standpoint. This is because the selected subject is prepared in a variety of approaches and ways. Additionally, the shown style creates concerns regarding the legislation and ambiguous perspectives on it. Clearly, no detailed discussion of the range of issues and styles in visual arts was conducted considering recent changes. As such, this article will outline the issues and styles mentioned in the fatwas and guidelines that have been issued. All fatwas and guidelines pertaining to visual arts were found using the process of assembling the highlights of the structured and methodical study. As a result of these observations, only a few categories of subjects have been covered, including humans, animals, plants, religious symbols, and human-made equipment; and the style discussed focuses exclusively on the mode of depiction. Recommendations to researchers interested in this work include conducting extensive qualitative research. Keywords: Fatwa, Subject, Style, and Visual Arts